2019
DOI: 10.1002/aoc.4836
|View full text |Cite
|
Sign up to set email alerts
|

Controlled isoprene polymerization mediated by iminopyridine‐iron (II) acetylacetonate pre‐catalysts

Abstract: A ligand controlled stereoselective polymerization of isoprene has been developed. A series of (aryl/alkyl)‐iminopyridine iron (II) acetylacetonate complexes: (aryl = Ph Fe1; alkyl = CH2Ph Fe2, CH (Ph)2 Fe3, CH (Me)2 Fe4, C (Me)3 Fe5, C (Me)2CH2C(Me)3 Fe6), has been prepared in which steric and electronic substituents systematically modified to investigate their influences for isoprene polymerization. The molecular structure of representative complex Fe2 was confirmed by single crystal X‐ray diffraction and, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Subsequently, Wang and collaborators described the effect of the auxiliary ligand in the iron-based iminopyridyl complexes by replacing both chloride anions by two acetylacetonato (acac) groups (Figure 2(C)) [27]. In the presence of an excess of MAO, the polyisoprene prepared with the (iminopyridyl)Fe(acac) 2 system bearing N - tert -octyl substituents showed a good trans -1,4 stereo-regularity (>87%) with an activity five times higher than that of the related chlorinated iron complex.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Wang and collaborators described the effect of the auxiliary ligand in the iron-based iminopyridyl complexes by replacing both chloride anions by two acetylacetonato (acac) groups (Figure 2(C)) [27]. In the presence of an excess of MAO, the polyisoprene prepared with the (iminopyridyl)Fe(acac) 2 system bearing N - tert -octyl substituents showed a good trans -1,4 stereo-regularity (>87%) with an activity five times higher than that of the related chlorinated iron complex.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of complex V1 : The suspension of ligand L1 [ 38 ] (260 mg, 1.3 mmol, 1.0 equiv.) in dry dichloromethane (5 ml) was added slowly to a suspension of VOCl 3 (230 mg, 1.3 mmol, 1.0 equiv.)…”
Section: Methodsmentioning
confidence: 99%
“…[ 33 ] Recently, iminopyridine ligands have attracted significant interest because of their easy preparation, and thus are widely used in transition metal catalyzed reactions. [ 34–41 ] In the present study, various alkyl‐ and aryl‐substituted novel iminopyridine vanadium complexes were synthesized and studied their catalytic capacity for isoprene polymerization. The effects of polymerization conditions and ligand moiety on the catalytic activity, regioselectivity, and properties of polymer were investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…For example, rare-earth metal and titanium catalysts afforded cis -1,4 or trans -1,4 polyisoprene with up to 98% selectivity [11,12,13,14,15]. In addition, some late transition-metal catalysts were also studied for isoprene polymerization, such as well-defined Fe and Co complexes [16,17,18,19,20,21,22,23]. However, the polymerization of isoprene with mid-transition metal-based catalysts remains less explored.…”
Section: Introductionmentioning
confidence: 99%
“…It is noticed that iminopyridine ligands are widely studied for many catalytic reactions, due to their facile synthesis and easy to control the catalytic performance by means of different substituents [19,20,21,23]. To extend this study, herein, we reported the synthesis of a series of iminopyridine vanadium(III) complexes and employed as catalysts for isoprene polymerization.…”
Section: Introductionmentioning
confidence: 99%